(untitled) (Research, Society and Development, 2021)
Objective: to verify the relationship between clinical manifestations and social, reproductive and pregnancy-related aspects in women and to prepare nursing diagnoses. Method: cross-sectional research with 30 pregnant women during prenatal in a northeastern city using the State - Trait Anxiety Inventory and a form for clinical manifestations of generalized anxiety disorder, with descriptive and inferential analysis. Results: There were statistical relations between number of prenatal visits and nervousness, sweating with ethnicity and with women with less than 20 weeks gestational age. Higher income was protective factor for dizziness and more than six prenatal visits is a protective factor for fear. Conclusion: Special attention to the clinical manifestations of anxiety should be given to non-white women over 26 years of age. Nursing diagnoses such as impaired sleep and altered rest pattern should be incorporated into the primary care plan.